Biodiversity, biopiracy and biopolitics the global perspectives - Chauhan, Surender Singh (Delhi Kalinga, 2001)
Biodiversity, Biopiracy and Biopolitics were the key issues of debate at the Rio Earth Summit in 1992, which led to the formation of two distinct blocks of "biological powers" the North nation rich in biotechnology and the South nation rich in biodiversit
Keywords: Biological diversity; Biopolitics; Ecological netrogeneity; Sociobiology